Erfolgsfaktoren der Hochschulweiterbildung. Issue 10 (18th July 2014) - Meschke, Stephan; Gutte, Heiner
<x xml:space="preserve">Abstract</x> A new program of the Federal Ministry of Education and Research is to strengthen the innovative potential of the new federal states. It includes the pooling of expertise as well as the possibility to apply research results in the industry. However, the transfer of knowledge from research projects has been difficult. Therefore, a key focus in the German Centre for Energy Resources is the investigation of continuing education capabilities under the name Professional Schools. Here, the objectives as well as selected results relating to key success factors in continuing education will be highlighted.